Compiling Exceptions Correctly - Hutton, Graham; Wright, Joel (Springer Lecture Notes in Computer Science, 2004)
Exceptions are an important feature of modern programming languages, but their compilation has traditionally been viewed as an advanced topic. In this article we show that the basic method of compiling exceptions using stack unwinding can be explained and verified both simply and precisely, using elementary functional programming techniques. In particular, we develop a compiler for a small language with exceptions, together with a proof of its correctness.